Dynamic surface disturbance rejection control for electro-hydraulic load simulator. (1st December 2019) - Jing, Chenghu; Xu, Hongguang; Jiang, Jihai
Highlights: A state space model of electro-hydraulic load simulator is established. State and disturbance observers are designed. A composite disturbance rejection control using dynamic surface is developed. It is proved that all signals are semiglobally uniformly ultimately bounded. Experiments verify the high-performance nature of the proposed control strategy. Abstract: The electro-hydraulic load simulator is a typical torque servo system that requires high accuracy and high frequency response. But it is subjected to actuator's motion disturbance, parametric uncertainties and unmodeled dynamics. In this paper, a novel dynamic surface disturbance rejection control with synchronous compensation is proposed to improve the torque tracking performance of electro-hydraulic load simulator. The proposed controller is designed using dynamic surface approach. Synchronous compensation is used to eliminate the main disturbance caused by actuator's motion, which could decouple the tested system and the load simulator. A state and disturbance observer is proposed for estimating lumped disturbances. The close-loop system with the proposed controller achieves high precision and strong robustness. It is proved that estimation errors of observer and tracking errors of close-loop system are bounded. Extensive experiments are carried out to verify the high-performance nature of the proposed control strategy.